A study on the electrical energy consumption characteristic of urban household in Klang Valley, Malaysia - Ng, Wai Tuck (Kulliyyah of Architecture & Environmental Design, International Islamic University Malaysia, 2012)
Is Malaysian used too much of electrical energy, especially by household in urban area? The aim of this research is to investigate the current pattern and characteristic of Malaysia urban household electrical energy consumption. In year 2005, a research on the Malaysia urban household electricity consumption was carried out and found that the consumption rate is 2204 kWh/year. Based on those findings, a projection was done for year 2010 with a projected consumption of 3707 kWh/year or 68% increment within 5 years. All 14 items of electrical appliances are expected to increase in consumption especially air conditioner day time, which is expected to increase about 7 times from 54 kWh/ year to 369 kWh/ year. However, air conditioner night time was expected to take the lead in total consumption with 871 kWh/year or about ¼ of a household consumption. The hypothesis of this research is the urban household electrical energy consumption has direct relationship with the standard of living. Household with higher income will consume more electrical energy than the lower income household. The methodology of this research is by conducting case studies on 30 houses within Klang Valley to find out the current electricity consumption. 3 types of houses were chosen - bungalow, terrace house and condominium from various townships within Klang Valley. 30 randomly pick up samples were: 21 samples of terrace houses, 7 from condominium and 2 from bungalows. To enable comparison with the projected scenario, similar 14 items of electrical appliances includes refrigerator, rice cooker, water heater, washing machine, dryer, iron, fan, television, radio, air conditioner night time, air conditioner day time, lighting, vacuum cleaner and computers were selected for this study. No addition or new appliances are considered to maintain consistency. General information of the household such as household income, type of house, house built-up area and household size were collected as a measurement to the standard of living. A comprehensive study was carried out on the daily electricity consumption, trend and habit of electricity usage, and the relationship between lifestyle and electricity consumption. The average yearly electrical energy consumption collected from 30 samples is 6876 kWh/year for year 2011 or 3169 kWh higher than the projection of 3707 kWh/year. In comparison to the consumption in year 2005 of 2204 kWh/year, there is an increment of 4672 kWh/year or 200% of increment within six years. When analysing the above increment relate to style of living, the study found that the electricity consumption rate has direct relationship with the standard of living. The higher the standard of living, electrical energy consumption of the household will be higher.The above tremendous increment reflected the electricity consumption in Malaysia, especially in urban area has grown in a very fast pace beyond the projected scenario. This definitely will trigger the alarm of energy crisis in Malaysia. Green technologies are required to be introduced into house design, either passive approach or active approach to reduce the electrical energy consumption.